SYNERGY OF ACTIVITY-BASED COSTING AND TARGET COSTING AS A STRATEGIC PILLAR OF COST EFFICIENCY IN OPTIMIZING PROFITABILITY: A CASE STUDY ON PT MOMENTUM VELO INOVASI (2020–2024) - Anggianto Nugroho; Nofryanti; Holiawati (ZILLZELL MEDIA PRIMA, 2025)
PT Momentum Velo Inovasi is a clothing manufacturing company that faces the challenge of continuously improving cost efficiency in order to remain competitive and earn optimal profits. However, the company still uses traditional cost calculation methods that are less accurate in charging costs to products. This causes cost information to be inaccurate and affects pricing decisions as well as profit levels. This problem shows that there is a gap between the company's need for more accurate cost information and the methods that have been used. In fact, the Activity Based Costing and Target Costing methods have been proven to be able to provide more accurate cost information and drive efficiency from the early stages of production. Research on the synergy of these two methods in improving cost efficiency and profitability in medium-sized companies is still rare, especially in the convection industry. This research uses a qualitative approach with a case study at PT Momentum Velo Inovasi during 2020 2024. Data was collected through interviews, observations, and documentation. The data analysis technique was carried out by comparing the results of cost calculations using traditional methods, Activity Based Costing, and Target Costing, then analyzed to see the effect on cost efficiency and company profits. The results of the study show that the combined application of Activity Based Costing and Target Costing is able to provide more precise cost information, encourage efficiency in production, and help companies increase profits sustainably.